Mozart's piano concerto's: Dramatic dialogue in the age of enlightenment - Keefe, Simon P. (Oxford Boydell & Brewer, 2001)
The interactive relationship between the piano and the orchestra in Mozart's concertos is an issue central to the appreciation of these great works, but one that has not yet received serious attention, a gap which this new study seeks to remedy by exploring the historical implications and hermeneutic potential of dramatic dialogue.The author shows that invocations of dramatic dialogue are deeply ingrained in late-eighteenth-century writings on instrumental